STRATEGI PENGEMBANGAN USAHA PUPUK ORGANIK PADA UD DARMA PURI FARM DI DESA TANGKAS, KECAMATAN KLUNGKUNG, KABUPATEN KLUNGKUNG - Yuni Erawati, Ni Made; Suamba, I Ketut; Sri Astiti, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS, 2018)
Fertilizer business is one of the business in agriculture proper to be developed. This can be seen from the high demand for organic fertilizer to make business people. Glance at promising business opportunities. The success of the organic fertilizer business is influenced by the strategy development . The purpose of this research is to formulate strategic alternatives and strategic priorities.         Variables used in this study are the internal and external environment variables environment variables. Collection methods used were interviews, field observations, questionnaires, documentation and FGD (Focus Group Discussion) data . Data analysis methods used are SWOT Analysis and QSPM Analysis The results showed that there were four alternative strategies in the order of priority, namely (1). Trying to maintain and improve the quality of organic fertilizer. (2). Maintain old partners and explore new partnerships. (3). Improve the promotion strategy by utilizing information technology that is increasingly advanced. (4). Expand market share. The right priority strategy for marketing organic fertilizer at UD Darma Puri Farn is expanding market share which is the first choice among the four other strategies. A few things can be advised of the results of this study are as follows: (1). By utilizing media and good online marketing strategies , it is expected to increase sales without limitation of space and time. In addition, an increase in SEO (Search Engine Optimization) is also needed to make it easier for cyberspace customers to find organic fertilizer products to be marketed. (2). In order for business to develop, what must be done is increasing the means of production, efficiency, and productivity through a work system aimed at improving the production process, as well as improving the quality of human resources in the workforce through education. and training. (3). To develop a business, it needs support from all elements, not only from the internal side of the business actor but also the role of government in supporting business development. It is hoped that the government can provide its support by providing entrepreneurship education to business people through guidance and counseling to improve the ability of small businesses to become resilient and independent businesses, as well as providing business capital assistance to increase the desire of business people to develop his business.